ANALISIS CAMEL DALAM MENILAI TINGKAT KESEHATAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - MARSINTA JUNIARTI ARITONANG; HIKMAH . (JURNAL ILMIAH KOHESI, 2020)
This study aims to determine the level of banking health in terms of the CAMEL analysis. The design of this research isdescriptive with quantitative research type. The data collection method in this research is the documentation method. Theanalysis technique used in this study is the analysis of bank financial statements. The results showed that a total of 15commercial banks that became the study sample showed "very healthy" results in terms of Capital (Capital Adequacy Ratio)ie with an overall average of 22.4%. In terms of Assets (Earning Assets Quality) in the "quite healthy" category which is3.32%. In terms of management (Net Profit Margin) in the category of "unhealthy" with an average total of 50.61%. In termsof Earning (Revenue) measured through the ROA and BOPO ratios which show the category of "very healthy" for the ROAratio with an average total of 4.32% and the BOPO ratio in "very healthy" conditions with an average total of 87.08% . Interms of Liquidity, it is measured by the Loan to Deposit Ratio, which is in the "quite healthy" category with an average totalof 87.99%.